Chishao (Paeoniae Radix Rubra) alleviates intra-hepatic cholestasis by modulating NTCP in rats - Sun, Xiaoqi; Fang, Jing; Fang, Nanyuan (Frontiers in Pharmacology, 2024)
Background: Cholestasis is a common pathological manifestation dominated by accumulation of potentially toxic biliary compounds. Na+-taurocholate cotransporting polypeptide (NTCP) plays a critical role in protection from cholestasis and can be targeted therapeutically. Chishao (Paeoniae Radix Rubra) is a clinically efficacious agent for treating cholestasis, but the underlying mechanism has not been fully clarified. Objective: To evaluate the effects of Chishao on the expression of NTCP in rats with alpha-naphthylisothiocyanate (ANIT)-induced cholestasis. Methods: Chishao extracts were obtained by water decoction. Cholestasis model induced by ANIT in rats were established. Thirty rats were divided into five groups: control group (C), ANIT model group (M), 10 g/kg Chishao group (LD), 20 g/kg Chishao group (MD) and 40 g/kg Chishao group (HD). The levels of serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin (TB), direct bilirubin (DB), alkaline phosphatase (ALP) and total bile acid (TBA) were detected. The mRNA and protein expression of NTCP, multidrug resistance associated protein 2 (MRP2) and bile salt export pump (BSEP) were detected by reverse transcription qPCR and Western blotting respectively. To assess the effects of Chishao on NTCP, MRP2 and BSEP localized at the membrane of hepatocytes, an in vitro experiment involving primary hepatocytes was conducted via the utilization of laser scanning confocal microscopy. Results: The extracts of Chishao significantly improved serum ALT, AST, ALP, TB, DB and TBA (P<0.05), especially ALP in the HD group (P<0.01). The histological pathological findings were also reversed in LD, MD and HD groups. The mRNA level of MRP2 was significantly down-regulated after treatment with ANIT, whereas it was reversed in MD and HD groups (P<0.05). The mRNA expression of NTCP was significantly down-regulated after ANIT treatment, but dramatically up-regulated in the HD group. The expressions of BSEP and MRP2 were similar, but that of NTCP decreased after ANIT treatment, which was reversed significantly by Chishao extracts in a dose-dependent manner. The expression of NTCP in hepatocytes from rats increased dose-dependently after Chishao treatment in vitro. Conclusion: Chishao extracts can improve the serum and histological performances of intra-hepatic cholestasis caused by ANIT, probably by working on transporter in liver cell membranes.